Larval production by crossbreeding and artificial insemination of freshwater prawns - Soundarapandian, P; Kannupandi, T (Indian Journal of Fisheries, 2011)
Interspecific crossing has been attempted between Macrobrachium malcolmsoniiand M. rosenbergii two cultivable freshwater prawns. The respective femalessuccessfully produced viable larvae. The hatching rate and survival percentageincreases with increase in size of both the species and it was comparatively higherin M. rosenbergii females. In intraspecific insemination trials, three M.malcolmsonii females produced viable larvae and another three shed their eggs.However, four M. rosenbergii females produced viable larvae and two shed theireggs. In interspecific insemination trials, females shed their eggs after about 6to 8 days of incubation.